Membrane Localization of Pyrene-Trehalose Conjugates (PYRETs) - Hagwood, Abigail (East Carolina University, 2018)
The disaccharide trehalose is found in many organisms that can survive in extremely cold or dry environments. According to the “hydration hypothesis,” trehalose interacts with the glycerol/phosphate regions of lipid bilayers and displaces water molecules, preventing ice crystals from puncturing the cell when frozen. In order to control the depth of trehalose penetration into membranes, we have attached the nonpolar fluorophore pyrene to trehalose via one-, three-, and five-carbon spacers. The conjugates, which we call PYRETs, are sufficiently soluble in ethanol-water to be purified by reversed-phase HPLC. Proton NMR showed low symmetry and integrations consistent with a single pyrene anchor per disaccharide unit. The effects of PYRETs on membrane dynamics is shown by fluorescence spectroscopy and differential scanning calorimetry. Long-term, PYRETs may be useful in cryopreservation of red blood cells.
Keywords: trehalose; pyrene; membrane localization; hydration hypothesis